Analysis of metabolites in young and mature Docynia delavayi (Franch.) Schneid leaves using UPLC-ESI-MS/MS - Xia,Xi; Chen,Can; Yang,Lin; Wang,Yuchang; Duan,Anan; Wang,Dawei (PeerJ, 2022)
Docynia delavayi (Franch.) Schneid is a plant used both as food and traditional folk medicine. The leaves of D. delavayi are rich in polyphenols, plants with phenolic content are known to be extremely beneficial in terms of human nutrition. In the present study, we used metabolome technology (UPLC-ESI-MS/MS) to examine the young and mature D. delavayi leaves on metabolites changes, which were then analyzed and compared. As a result, 477 metabolites (including 111 flavonoids, 47 others (consisted of nine vitamin, 18 saccharides and alcohols, and 20 unassigned metabolites), 71 phenolic acids, 52 amino acids and derivatives, 18 alkaloids, 61 lipids, 24 terpenoids, 33 nucleotides and derivatives, 18 lignans and coumarins, 12 tannins, 30 organic acids) were identified, of which 281 differentially accumulated metabolites, including 146 up-regulated metabolites and 135 down-regulated metabolites. The result of clustering and PCA analyses showed that young and mature leaves were separated, which indicated that there was a great difference in metabolites between young and mature leaves. Meanwhile, we also found that both young and mature leaves displayed unique metabolites with important biological functions. KEGG enrichment analysis showed that 90 of the differential metabolites were mainly concentrated in 68 KEGG pathways. The result will greatly complement the existing knowledge on the D. delavayi leaves for lays a foundation for subsequent development and utilization.
Keywords: Docynia delavayi; UPLC-ESI-MS/MS; Metabolites